2020
DOI: 10.23986/afsci.88904
|View full text |Cite
|
Sign up to set email alerts
|

Mixing fresh-cut baby green and red leaf lettuce from soilless cultivation preserves phytochemical content and safety

Abstract: The objective of this study was to evaluate the impact of different mixtures of two fresh-cut baby lettuce (Lactuca sativa L. var. crispa cv. Lollo Bionda [LB] and cv. Lollo Rossa [LR]) cultivars on lettuce phytochemical composition during postharvest. Lettuces were grown in a soilless culture system with continuous flotation (FL) in a greenhouse, mixed at harvest and packaged in polypropylene bags and stored at 4 °C for 9 days (d9). Mixes were made of 100, 75, 50, 25 and 0% of LB, respectively. The results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…These data clearly testify the increasing demand of consumers for health-promoting natural products and fresh foods. Green leafy vegetables, in particular, can provide minerals, dietary fibers, vitamins, and many other antioxidant metabolites essential for a balanced diet that reduces the risk of oxidative stress-related aging and degenerative diseases while promoting psychophysical well-being [2][3][4][5]. In Europe, the consumption of high quality ready-to-eat (RTE) 100% edible leafy greens has reached Agronomy 2021, 11, 1040 2 of 16 a turnover of about 600 million Euros [6], and Italy ranked as the leader in Europe for the production of RTE leafy greens with about 15,000 ha and 160 kilotons of greenhouse production per year [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…These data clearly testify the increasing demand of consumers for health-promoting natural products and fresh foods. Green leafy vegetables, in particular, can provide minerals, dietary fibers, vitamins, and many other antioxidant metabolites essential for a balanced diet that reduces the risk of oxidative stress-related aging and degenerative diseases while promoting psychophysical well-being [2][3][4][5]. In Europe, the consumption of high quality ready-to-eat (RTE) 100% edible leafy greens has reached Agronomy 2021, 11, 1040 2 of 16 a turnover of about 600 million Euros [6], and Italy ranked as the leader in Europe for the production of RTE leafy greens with about 15,000 ha and 160 kilotons of greenhouse production per year [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in vitro digestion of both red beet and amaranth microgreens, produced a significant increase in total phenolic content (36-88%), antioxidants (6-43%), and total betalains (41-57%), with maximum levels observed when the material was stored for 10 days prior to digestion. Using different cultivation systems, Pignata et al [20] reported that after 9 days of storage at 4 • C, baby green and red leaf lettuce (Lactuca sativa L.) that were harvested from soilless cultivation systems retained its phytochemical content better than lettuce grown in traditional soil-based cultivation systems. The effects of genotype and harvesting day on phytochemical quantities were evaluated in two cultivars of loquat (Eriobotrya japonica) fruit [21].…”
Section: Pre-harvest Factors That Affect Changes In Phytochemicals During Storagementioning
confidence: 99%
“…The production of this type of product is increasingly being carried out by means of soilless cultivation systems (SCSs), which represent an efficient way of managing cultivation inputs and resources and allow a high product quality to be obtained [ 3 , 4 ]. BLV are rapidly becoming an important segment of the fresh-cut industry, thanks to their convenience, high value, unique sensory characteristics, and healthy phytochemicals, which are sources of minerals, vitamins, and antioxidants [ 1 , 5 , 6 , 7 ]. Therefore, the development of BLV is recommended because of their possible health benefits and excellent processing characteristics [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…BLV are rapidly becoming an important segment of the fresh-cut industry, thanks to their convenience, high value, unique sensory characteristics, and healthy phytochemicals, which are sources of minerals, vitamins, and antioxidants [ 1 , 5 , 6 , 7 ]. Therefore, the development of BLV is recommended because of their possible health benefits and excellent processing characteristics [ 6 ]. Nevertheless, BLV are highly perishable and susceptible to quality decay along the supply chain as their tender immature leaves have a higher respiration rate and active metabolism than fully mature ones [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation